THE INFLUENCE OF DIGITAL LITERACY TRAINING ON THE PREVENTION OF CYBERBULLYING AND THE PROMOTION OF HARMONIZATION IN VIRTUAL SPACES AMONG STUDENTS OF JABAL NOOR INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL - humaizi humaizi; Aulia Rahma Ritonga; Endah Rundika Pratiwi (OPINI: Journal of Communication and Social Science, 2025)
This study examines the effectiveness of digital literacy training in preventing cyberbullying and fostering virtual harmonization among students of Jabal Noor Integrated Islamic Junior High School. Using a quantitative pretest–posttest one-group design, the research involved 33 students from grades VII–IX who participated in a digital literacy training program. Data were collected through validated questionnaires measuring awareness of cyberbullying prevention and skills in maintaining ethical communication in virtual spaces. The results showed a significant increase in the average score from 64.33 (pretest) to 73.82 (posttest), with a mean difference of 9.49 points. A paired sample t-test yielded t = 20.06, p < 0.001, indicating a highly significant effect. The findings demonstrate that digital literacy training not only enhances students’ understanding of online ethics but also reduces the tendency to engage in cyberbullying while promoting inclusive and harmonious digital interactions.